Budaya Organisasi dan Kepuasan Kerja Terhadap Organizational Citizenship Behavior Melalui Komitmen Organisasi Sebagai Variabel Moderating - Kusumawardani, Mawar Ratih; Kurniawan, Brahma Wahyu (Akutansi Bisnis & Manajemen ( ABM ), 2018)
The results of this study indicate that: (1) Organizational culture has a significant influence on Organizational Citizenship Behavior, (2) Job satisfaction hasn’t influence on Organizational Citizenship Behavior, (3) Organizational culture has a significant influence on organizational commitment, (4) Job satisfactin hasn’t influence on organizational commitment, (5) Organizational Citizenship Behavior has a significant influence on organizational commitment, (6) Organizational culture has an indirrect influence on organizational commitment through Organizational Citizenship Behavior, and (7) Job satisfaction has an indirrect influence on organizational commitment through Organizational Citizenship Behavior.